IMPLEMENTASI BANTUAN PENDIDIKAN UNTUK ANAK JALANAN DI RUMAH PERLINDUNGAN ANAK â€œGRATAMAâ€ SEMARANG - Zuliani, Ani; Rahman, Maman; Tijan, Tijan (Unnes Civic Education Journal, 2015)
One of the rights of children are getting education so that they have enough opportunity to develop their selves and talents in accordance to their talents and interests. Normatively, the Republic of Indonesia ensure the welfare of children, including the right of children to get a decent education and teaching. But, the fact shows that the dropout rates in Indonesia, including that experienced by street children, are still high. A phenomena in the city of Semarang is the growing number of street children. Ironically, the existence of street children is often overlooked and ignored by most people. During this time, the governmentâ€™s efforts in addressing the problem of street children do not look up to. RPSA Gratama is one of the shelter that concerned about the fate of street children in Semarang. One of the programs is educational assistance program. RPSAs Gratama faces many challenges. this program. This study tries to find out the implementation of educational assistance programs in RPSAs â€œGratamaâ€ for street children in Semarang.